(untitled) (Journal of Pharmaceutical Negative Results, 2022)
BACKGROUND: Children are a vulnerable group in the society. They need special care to survive with good health. Rotavirus is one of the leading causes of diarrhoea among children under 5 years of age. It is responsible for approximately 37% of all diarrhoea-associated hospitalizations and 2,15,000 deaths annually.OBJECTIVES: To assess the level of knowledge and utilisation of Rotavirus vaccination among Rural mothers having children Under five years of age.METHODOLOGY: A Cross sectional study was conducted among 112 rural mothers having children under five years of age with a structured and validated questionnaire. The results were analysed using SPSS version 21.RESULTS: This study showed that Rural mothers with children under the age of five had poor level of knowledge regarding Rotavirus immunisation and more than half of them had not vaccinated their children when due. Younger maternal age, maternal illiteracy and low socioeconomic status were associated with low level of knowledge and poor vaccination status. Lack of Mothers' knowledge of Rotavirus vaccination and their vaccination status of their kids was found to have a very strong negative correlation.CONCLUSION: The study reveals the urgency in need of health education and motivation of the general public regarding Rotavirus vaccination, which will in turn help in high vaccination rates of the same and prevention of Rotavirus infections.